Hypotheses of forensics (Academic Journal of Internal Affairs, 2021)
The paper intoduces the concept and the several types of hypotheses used in criminalistics, the s.c. investigative theory and its relation to basic questions of criminalistic. The author considers the process of creating investigative theories as a mental event reconstruction in wider sense and raises attention to the most important basic principle during that process, the principle of reality. The study also introduces the applicability of the Occam’s razor philosophical approach, often cited in connection with the creation and evaluation of investigative theories. After introducing the contention of investigative theories, the author analyses the causes and negative consequences of the „sticking to an arbitrarily chosen investigative theory” attitude, as a typical failure in the criminal investigative process.
Keywords: investigative theory; basic questions of criminalistic; creating investigative theories; mental event reconstruction